Fibrolamellar Hepatocellular Carcinoma and Noncirrhotic Hyperammonemic Encephalopathy (2018)
Fibrolamellar hepatocarcinoma is an infrequent liver tumor, currently considered to be a variant different from hepatocarcinoma. The differences lie in genomic alterations, a greater prevalence of fibrolamellar hepatocarcinoma in young patients, and its lack of association with underlying liver disease. The clinical presentation is unspecific, with symptoms ranging from abdominal pain, malaise, and weight loss to atypical manifestation which include hyperammonemic encephalopathy. We present the case of a 33-year-old woman with no prior medical history who presented with a coma and a diagnosis of inoperable fibrolamellar hepatocarcinoma requiring a cadaver donor transplant. While she was on the waiting list, she received hemofiltration and ammonium benzoate treatment, with progressive improvement in her state of consciousness.